Do clones dream of absent father(s)? Biotechnologia i metafizyka w powieści Nie opuszczaj mnie Kazuo Ishiguro i jej filmowej adaptacji - Korczarowska, Natasza (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article deals with metaphysical aspects of dystopian vision of posthuman and racist socjety presented in Kazuo Ishiguro’s novel Never Let Me Go and its film adaptation. The controversial issue of cloning provokes fundamental questions of what constitutes our existence as human beings and what is the source of overpowering sense of solitude and orphanhood in the “fatherless” world. These questions are being answered in the context of biopolitics (Foucault, Habermas) and its ethical consequences. The paper is intended as a contribution to the ongoing discussion of the human condition and our relation to other beings: machines, animals and… clones.